Retrospective analysis of ventilation strategies for blunt pulmonary trauma patients: comparing the effectiveness of synchronized intermittent mandatory ventilation, continuous positive airway pressure, and pressure-controlled ventilation - Wu, Lanlan; Hu, Yanhua; Lu, Yanwen (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the efficacy of various ventilation approaches to the treatment of patient with patients with severe blunt chest trauma. Method: The retrospective study was conducted at the Cardiorespiratory Syndrome Ward of the First People’s Hospital of Linping District, Hangzhou, China, and comprised data of patients with blunt pulmonary trauma admitted from December 2019 to February 2023. The patients were divided into three groups based on the ventilation support mode. Group 1 received synchronised intermittent mandatory ventilation + positive end-expiratory pressure, Group 2 received continuous positive airway pressure + pressure support ventilation, and Group 3 recieved pressure-controlled ventilation. Clinical curative effect, respiratory mode parameters, and blood gas analysis indicators of the groups were compared before and after the treatment. Data was analysd using SPSS 20. Results: Of the 227 patients, 71(31.3%) were in Group A; 62(87.3%) males and 9(12.7%) females with mean age 69.6±5.9 years. There were 74(32.6%) patients in Group 2; 59(79.7%) males and 15(20.3%) females with mean age 71.2±6.2 years. In Group 3, there were 82(36.1%) patients; 61(74.4%) males and 21(25.6%) females with mean age 69.0±6.0 years (p>0.05). Most patients 146(64.32%) recovered with no significant differences in treatment effect across the groups (p>0.05). Group 2 showed significant differences in respiratory parameters and blood gas indicators compared to the other groups (p<0.001). Conclusion: While all the three ventilation strategies had comparable treatment effect, continuous positive airway pressure + pressure support ventilation was associated with the most favourable respiratory parameters and blood gas analysis indicators. Key Words: Pulmonary injuries, Ventilation techniques, Comparative effectiveness, Blood gas analysis.